2020
DOI: 10.1002/aur.2265
|View full text |Cite
|
Sign up to set email alerts
|

The Incredible Years Autism Spectrum and Language Delays Parent Program: A Pragmatic, Feasibility Randomized Controlled Trial

Abstract: Behavior problems in children with autism spectrum disorders (ASD) are common and particularly stressful for parents. This study aimed to examine the feasibility of delivering a parenting program in existing services, and the feasibility of conducting a future large‐scale Randomized Controlled Trial evaluation of the effectiveness of the intervention. Parents of children aged 3–8 years with a diagnosis of ASD, or strongly suspected ASD were eligible to participate. A multicenter, pragmatic, feasibility randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…removal of social attention), but may elicit different reactions from autistic children. Furthermore, Williams et al (2020) found that some parents found the child-led play component of the DPICS challenging due to difficulties in getting their autistic child to engage. Measures may therefore require modification in order to be reliable and valid assessments of child and parenting behavior in autism.…”
mentioning
confidence: 99%
“…removal of social attention), but may elicit different reactions from autistic children. Furthermore, Williams et al (2020) found that some parents found the child-led play component of the DPICS challenging due to difficulties in getting their autistic child to engage. Measures may therefore require modification in order to be reliable and valid assessments of child and parenting behavior in autism.…”
mentioning
confidence: 99%
“…The control groups consisted of waitlist or other passive control conditions in 11 of the studies ( 31 , 36 , 37 , 42 , 45 47 , 49 , 51 , 52 , 54 ); treatment/management as usual in 10 of the studies ( 25 , 28 , 30 , 32 , 39 , 40 , 43 , 44 , 48 , 53 ); an active control with a less extensive educational program, psycho-education, placebo parent-intervention in eight of the studies; and anti-psychotic medicine (risperidone) alone in a single study ( 26 , 27 , 29 , 33 35 , 38 , 41 , 50 ). Four studies ( 36 , 41 , 47 , 54 ) either did not report data predefined as primary or secondary outcomes in the present context or did not report data in a manner for them to be included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It also focuses on how to use positive discipline to set limits and handle misbehavior. A pragmatic randomized controlled trial has been recently published, supporting the feasibility of delivering this intervention in the UK National Health Service (NHS), and showing good levels of acceptability, compliance and delity to the program (33,34).…”
Section: Group Interventions (The Incredible Years Autism Spectrum Anmentioning
confidence: 98%